Comparative analysis of off-road vehicle crashes in children: motorcycles versus quad bikes. Issue 6 (13th July 2022) - Mulligan, Christopher S; Adams, Susan; Moeller, Holger; Whyte, Tom; Soundappan, Soundappan S V; Brown, Julie
Abstract : Objective: To characterise and compare off-road motorcycle and quad bike crashes in children in New South Wales (NSW), Australia. Methods: A retrospective, cross-sectional study was performed of children aged 0–16 years, admitted to hospitals in NSW, from 2001 to 2018 following an injury sustained in an off-road motorcycle or quad bike crash, using linked hospital admissions, mortality and census data. Motorcycle and quad bike injuries were compared regarding: demographics; incidence; body region injured and type of injury; injury severity based on the survival risk ratio; length of stay and mortality. Results: There were 6624 crashes resulting in hospitalisation; 5156 involving motorcycles (77.8%) and 1468 involving quad bikes (22.2%). There were 10 fatalities (6 from motorcycles and 4 from quad bikes). The rates of injury declined over the study period for motorcycles, but not for quad bikes. Motorcycle riders were more likely than quad bike riders to have lower limb injuries (OR 1.49, p<0.001) but less likely to have head/neck (OR 0.616, p<0.001), abdominal (OR 0.778, p=0.007) and thoracic (OR 0.745, p=0.003) injuries. Quad bike crashes resulted in higher injury severity (mean International Classification Injury Severity Score 0.975 vs 0.977, p=0.03) and longer hospital stay (mean 2.42 days vs 2.09 days, p=0.01). Conclusions: There are significant differences between quad bike and motorcycle crashes in injury type and affected body region. While quad bike injuries in children were more severe, there were almost four times more hospitalisations from motorcycles overall. The overall larger burden of motorcycle crashes suggests a greater focus of injury prevention countermeasures for two-wheeled riders is needed.